The Fading (Lost) Colour of Reformed Theology in Reformed Churches in Indonesia and the Urgency of Reformation in the 21st Century - Lumintang, Stevri P.N. Indra (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to reveal the fading (lost) colour of Reformed theology in churches with Reformed backgrounds or patterns in Indonesia as a reason for the urgent reformation agenda at the beginning of the 21st century (today). This objective is motivated by the gap between Reformed theology that faithfully upholds the truth of the Bible and the compromise of church leaders and/or theologians that results in the fall of the church and the loss of hope for the world (tragic). The research used historical-theology method, with the finding that the fading colour of Reformed theology in some Reformed churches denominations in Indonesia started since the entry of Reformed theology and churches that have been